Pembelajaran Bahasa Inggris Anak Sekolah Dasar Pada Program Belajar Dari Rumah Di Desa Sidomulyo - Theresia Budi Sucihati Tere; Restina Dwi Cahyani (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
English lessons are considered difficult for junior high school children because they never get these lessons in elementary school. In addition, learning, which was originally carried out face-to-face (offline), has changed to online or is carried out boldly during the COVID-19 pandemic. Learning assistance from home (BDR) must be carried out so that elementary school children in grades 1-6 in Sidomulyo Village can be technologically literate, especially in the use of gadgets and the internet to learn English online. The BDR Learning Method applies the Discovery-Inquiry Learning (DIL) model. This model is a combination of the discovery learning model and the inquiry learning model. The results of the survey during BDR showed that many children feel enthusiastic and interested in participating in learning. In addition, the expertise in operating cellphones to learn from YouTube, Google Drive, and Whatsapp media is considered easier to apply even though 30% of them still have some problems with internet connection.